AN ANALYSIS OF NARRATIVE TEXTS IN TEXTBOOKS USED BY EIGHTH GRADE STUDENTS (Systemic Functional Linguistics Perspective) - Veronika Titin Suhartini (Journal of English and Education, 2016)
This paper entitled “Analysis of Narrative Texts in Textbooks Used by Eighth grade Students (Systemic Functional Linguistics Perspective)” is aimed to reveal to what extent Narrative texts in two selected English textbooks fulfill the criteria of Narrative text and to find out the similarities and differences of Narrative texts between two selected English textbooks. The study employed descriptive qualitative method. The data were in this study were six Narrative texts taken from two selected textbooks. The data analysis was done by investigating schematic structure, social purpose and linguistic features by using Transitivity system. The results of analysis show that in some extent (1) four out of six Narrative texts have fulfilled the schematic structure criteria namely Orientation, Complication, and Resolution; (2) five out of six Narrative texts fulfill the social purposes; and (3) six out of six Narrative texts fulfill the linguistic features. To sum up, Narrative texts in two textbooks are similar in terms of linguistic features and process types, whereas the differences were found in terms of social purpose and schematic structure.